The Aquaporin 5 −1364A/C Promoter Polymorphism Is Associated With Cytomegalovirus Infection Risk in Kidney Transplant Recipients - Rahmel, Tim; Nowak, Hartmuth; Frisenda, Sandra; Rump, Katharina; Koos, Björn; Schenker, Peter; Viebahn, Richard; Adamzik, Michael; Bergmann, Lars (Frontiers in Immunology, 2019)
Background: The aquaporin 5 (AQP5) −1364A/C promoter single nucleotide polymorphism affects key mechanisms of inflammation and immune cell migration. Thus, it could be involved in the pathogenesis of cytomegalovirus infection. Accordingly, we tested the hypothesis that the AQP5 promoter −1364A/C polymorphism is associated with the risk of cytomegalovirus infection in kidney transplantation recipients. Methods: We included 259 adult patients who received a kidney transplant from 2007 and 2014 in this observational study. Patients were genotyped for the AQP5 promoter −1364A/C single nucleotide polymorphism and followed up for 12 months after transplantation. Kaplan–Meier plots and multivariable proportional hazard analyses were used to evaluate the relationship between genotypes and the incidence of cytomegalovirus infection. Results: The incidences of cytomegalovirus infection within 12 months after kidney transplantation were 22.9% for the AA genotypes (43/188) and 42.3% for the AC/CC genotypes (30/71; p = 0.002). Furthermore, multivariable COX regression revealed the C-allele of the AQP5 −1364A/C polymorphism to be a strong and independent risk factor for cytomegalovirus infection. In this analysis, AC/CC subjects demonstrated a more than 2-fold increased risk for cytomegalovirus infection within the first year after kidney transplantation (hazard ratio: 2.28; 95% CI: 1.40–3.73; p = 0.001) compared to that in individuals with homozygous AA genotypes. Conclusions: With respect to opportunistic cytomegalovirus infections (attributable to immunosuppression after kidney transplantation), the C-allele of the AQP5 −1364A/C promoter polymorphism is independently associated with an increased 12-month infection risk. These findings emphasize the importance of genetic variations as additional risk factors of cytomegalovirus infection after solid organ transplantations and might also facilitate the discovery of novel therapeutic targets.